Biogeochemistry and algal communities in the annual sea ice at Terra Nova Bay (Ross Sea, Antarctica) - GUGLIELMO L.; CARRADA G. C.; CATALANO G.; COZZI S.; DELL'ANNO A.; FABIANO M.; GRANATA A.; LAZZARA L.; LORENZELLI R.; MANGANARO A.; MANGONI O.; MISIC C.; et al. (2004)
During the fifteenth Italian Antarctic expedition, in the framework of the Pack Ice Ecosystem Dynamics programme, we investigated structure and functioning of the sympagic communities in the annual pack ice at Terra Nova Bay (74 41.720 S, 164 11.630 E). From November 1 to November 30 1999, we collected intact sea ice cores and platelet ice samples at an interval of 3 days. Ice samples were analysed for inorganic nutrients concentrations, algal biomass and productivity, pigment spectra, extracellular enzymatic activities and bacterial carbon production, micro-algal and metazoan community structure. Autotrophic biomass in the bottom ice increased more than two orders of magnitude from the beginning to the end of November 1999 (i.e. from c. 1–400mg chlorophyll am3). In the same temporal interval, inorganic nutrients concentrations as well as dissolved organic matter sharply increased. Pigment spectra and microscopic analyses revealed that bottom ice communities were different from those of the platelet ice. The bottom-ice sympagic flora was represented almost exclusively by cryobenthic species, whereas platelet ice was characterised by the presence of both cryopelagic and cryobenthic species. Metazoan community in the bottom sea ice was largely dominated by copepods. In particular, the calanoiod Stephos longipes and the harpacticoid Harpacticus furcifer accounted for more than 90% of the sympagic fauna. In the bottom sea ice concentrations of phaeophorbides and other degraded phytopigments were low indicating that most of the sympagic flora was active. These findings suggest that grazing pressure might be only a minor factor controlling or regulating inorganic nutrient concentrations. Conversely, potential degradation rates of organic carbon mediated by extracellular enzymatic activity were very high and largely exceeded organic matter production by photosynthesis.